Corrigendum to “The pressure balancing act in geological storage: sharing the subsurface for the common good” [Int. Journal of Greenhouse Gas Control 151 (2026) 104610] - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah E. Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

Model based evaluation of dry rooms in battery production - Felix Buck; Kira Fischer; Nikolas Dilger; Sabrina Zellmer; Christoph Herrmann (Journal of Cleaner Production, 2026)

The pressure balancing act in geological storage: sharing the subsurface for the common good - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah Eileen Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

NfL and GFAP quantification and associations with mental health in recreational cannabis users—Results from the Swiss study on recreational cannabis access via pharmacies - Maximilian Meyer; C. Felix Mosandl; Adrian Guessoum; Oliver Herrmann; Lavinia Baltes-Flückiger; Eva-Maria Pichler; Amar Zadic; Aleksandra Maleska Maceski; Juan Francisco Vilchez Gomez; Kenneth M. Dürsteler; Felix Müller; Undine E. Lang; et al. (Molecular Neurobiology, 2026)

An ectomycorrhizal fungus alters developmental progression during endogenous rhythmic growth in pedunculate oak - Felix Zimmermann; Marie-Lara Bouffaud; Sylvie Herrmann; Marco Göttig; René Graf; Mika Tarkka; Lars Opgenoorth; Daniel Croll; Martina Peter; Benjamin Dauphin (Mycorrhiza, 2025)
Pedunculate oak ( Quercus robur L.), a long-lived forest tree species, forms symbiotic relationships with ectomycorrhizal (ECM) fungi, which can promote nutrient uptake, stress resilience, and growth. Like other tropical and temperate tree species, pedunculate oak exhibits endogenous rhythmic growth (ERG), a trait conferring the ability to repeatedly alternate root and shoot flushes as well as growth cessation as response to changing environmental conditions. However, the effects of different ECM fungal species on the ERG dynamics remain largely unknown. Here, we investigated the impact of two ECM fungi— Piloderma croceum , a basidiomycete previously shown to promote growth while not found in natural oak stands, and Cenococcum geophilum , an oak-native ascomycete with broad ecological range—on growth performance, biomass partitioning, and ERG patterns in a clonal oak system (clone DF159). By combining in vitro experiments with Bayesian modelling, we show that P. croceum promotes tree growth among treatments, without disrupting the endogenous growth rhythm. In contrast, C. geophilum , while showing high mycorrhization rates, led to reduced biomass accumulation and altered developmental progression through the ERG stages, especially by prolonging the steady state development stage—part of the root flush and characterized by peak net carbon assimilation. Co-inoculation revealed a competitive advantage of C. geophilum in root colonization, yet growth responses resembled those of the control. Our findings demonstrate that ECM species exert species-specific effects on biomass production and temporal development of plants, underscoring the functional importance of ECM fungi in shaping host development. Assessing these interactions provides new insights into the functional diversity of ectomycorrhizal symbiosis and can inform forest management strategies aimed at enhanced resilience in oak-dominated ecosystems under rapidly changing climatic conditions.

Urban–industrial symbiosis recommendation platform for urban factories: Leveraging historical exchange patterns through feature analysis for real‐world applications - Philipp Grimmel; Jan Felix Niemeyer; Chuan Fu Tan; Yajuan Sun; Yang Zhao; Nils Schöling; Zhiquan Yeo; Mark Mennenga; Vanessa Miriam Carlow; Christoph Herrmann (Journal of Industrial Ecology, 2025)
Since the beginning of industrialization, the economic viability of manufacturing companies relied on the exploitation of natural resources. From 2000 to 2019, the global consumption of raw materials surged by 65%, with 70% of these materials being non‐renewable. Addressing this unsustainable trajectory, the United Nations emphasizes “Responsible consumption and production” as a sustainable development goal (SDG 12), advocating for resource efficiency, circularity, and dematerialization of economic growth. In that context, industrial symbiosis (IS) emerges as a key strategy for sustainable industrial development. IS networks have demonstrated substantial environmental and economic benefits in supply chains. Urban areas, such as the Braunschweig region in Germany or Singapore, characterized by its diverse industries in close geographical proximity, present unique opportunities for IS. In parallel, there is a special demand to enhance the circular economy due to the high density of resource flows and the high dependency on external material supply and disposal. Against this background, this research introduces an IS recommendation system that relies on a knowledge database containing reported material exchange data from various industries. This system incorporates a knowledge‐based matching methodology, which identifies potential symbiotic relationships by evaluating the suitability of different waste stream patterns. Additionally, a hierarchical matching method is developed to suggest potential IS partners based on multicriteria decision support. The proposed method is implemented, tested, and validated through a case study in Braunschweig and Singapore. Finally, recommendations for action are derived, and the methodology is critically reviewed for its effectiveness and applicability.

Model-parallel Fourier neural operators as learned surrogates for large-scale parametric PDEs - Thomas J. Grady; Rishi Khan; Mathias Louboutin; Ziyi Yin; Philipp A. Witte; Ranveer Chandra; Russell J. Hewett; Felix J. Herrmann (Computers & Geosciences, 2023)

Multiphase-field modelling of crack propagation in geological materials and porous media with Drucker-Prager plasticity - Michael Späth; Christoph Herrmann; Nishant Prajapati; Daniel Schneider; Felix Schwab; Michael Selzer; Britta Nestler (Computational Geosciences, 2021)
A multiphase-field approach for elasto-plastic and anisotropic brittle crack propagation in geological systems consisting of different regions of brittle and ductile materials is presented and employed to computationally study crack propagation. Plastic deformation in elasto-plastic materials such as frictional, granular or porous materials is modelled with the pressure-sensitive Drucker-Prager plasticity model. This plasticity model is combined with a multiphase-field model fulfilling the mechanical jump conditions in diffuse solid-solid interfaces. The validity of the plasticity model with phase-inherent stress and strain fields is shown, in comparison with sharp interface finite element solutions. The proposed model is capable of simulating crack formation in heterogeneous multiphase systems comprising both purely elastic and inelastic phases. We investigate the influence of different material parameters on the crack propagation with tensile tests in single- and two-phase materials. To show the applicability of the model, crack propagation in a multiphase domain with brittle and elasto-plastic components is performed.

Enabling numerically exact local solver for waveform inversion—a low-rank approach - Rajiv Kumar; Bram Willemsen; Felix J. Herrmann; Alison Malcolm (Computational Geosciences, 2019)

P-V-T behavior of FeO(OH) and MnO(OH) - Felix Wiethoff; Klaus-Dieter Grevel; Bernd Marler; Julia Herrmann; Juraj Majzlan; Jens Kirste; Christian Lathe (Physics and Chemistry of Minerals, 2017)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)

Tracking genes of ecological relevance using a genome scan in two independent regional population samples of Arabis alpina - BÉNÉDICTE N. PONCET; DORIS HERRMANN; FELIX GUGERLI; PIERRE TABERLET; ROLF HOLDEREGGER; LUDOVIC GIELLY; DELPHINE RIOUX; WILFRIED THUILLER; SERGE AUBERT; STÉPHANIE MANEL (Molecular Ecology, 2010)

Cloning and functional analyses of the mouse tapasin promoter - Felix Herrmann; John Trowsdale; Christoph Huber; Barbara Seliger (Immunogenetics, 2003)